PERSEPSI KONSUMEN MENGENAI PERIKLANAN DAN PENGARUHNYA TERHADAP MINAT BELI DI MARKETPLACE SHOPEE - Sukaesih, Uuh; Utami Rohadini, Vemiana; Miswan, Miswan (Jurnal Industri Kreatif dan Kewirausahaan, 2024)
Advertising via mass media or social media requires large costs so that the advertising is attractive and effective. Effective advertising can help companies build positive perceptions among consumers so that they can maintain and increase purchasing interest to increase company revenue and profits. The research objectives are: 1. To find out consumer perceptions regarding the quality of Shopee marketplace advertising, 2. To find out about consumer buying interest in the Shopee marketplace, 3. To find out and analyze the influence of advertising on buying interest in the Shopee marketplace. In this research, it was conducted for consumers using the Shopee marketplace application with a sample size of 100 people, the questionnaire was sent via Google Form. The analysis model in this research uses descriptive statistics (average and percentage) and is continued with simple linear regression analysis. Based on the analysis results, namely: 1. Average Shopee marketplace advertising quality = 4.52 (highest value = 5), 2. Average purchase interest = 4.43 (highest value = 5), 3. Advertising has a significant effect and shows positive influence on buying interest in the Shopee marketplace.